Pengaruh Program Pemberdayaan Ibu Hamil di Komunitas Terhadap Kepatuhan Antenatal Care: Studi Pre-Eksperimental - Masliha Masliha (Lembaga Pengembangan Kinerja Dosen, 2025)
The expecting mother's participation in antenatal checkups can assist in maintaining the wellness of both the mother and the fetus. Nonetheless, Lower compliance shows an inadequate level of care in society. Objective: This study aims to evaluate the impacts of the pregnant women empowerment program on antenatal care compliance under the Jatisawit Health Center working area, Jatibarang District, Indramayu Regency. Method: One group pre-experimentation was the design for this study, consisting of pre-test and post-test. A total of 40 pregnant women were selected as the sample using purposive sampling. Questionnaires were instruments to gather information, while the Wilcoxon test was employed to analyze data. Results: Improvements in compliance with antenatal care examinations and respective empowerment program participation showed a significant result with a p-value of 0.000 (p <0.05). Conclusion: The pregnant women empowerment program improved compliance with antenatal care. The program should be expanded as it promotes better maternal health education and preventive health measures within the community.